The Role Of The Integrative Approach In Developing Theoretical Thinking In Future Educators - Gulbahor Kholmirzayeva (Peerian Journals Publishing, 2025)
his article analyzes the role and significance of an integrative approach in the process of developing theoretical thinking among future educators. It reveals how integrative teaching methods contribute to the deep acquisition of theoretical knowledge and its application in practice.
Keywords: theoretical thinking; integrative approach; educator